Indications and Types of Antibiotic Agents Used in 6 Acute Care Hospitals, 2009–2010: A Pragmatic Retrospective Observational Study. (12th October 2015) - Kelesidis, Theodoros; Braykov, Nikolay; Uslan, Daniel Z.; Morgan, Daniel J.; Gandra, Sumanth; Johannsson, Birgir; Schweizer, Marin L.; Weisenberg, Scott A.; Young, Heather; Cantey, Joseph; Perencevich, Eli; Septimus, Edward; et al.
Abstract : BACKGROUND: To design better antimicrobial stewardship programs, detailed data on the primary drivers and patterns of antibiotic use are needed. OBJECTIVE: To characterize the indications for antibiotic therapy, agents used, duration, combinations, and microbiological justification in 6 acute-care US facilities with varied location, size, and type of antimicrobial stewardship programs. DESIGN, PARTICIPANTS, AND SETTING: Retrospective medical chart review was performed on a random cross-sectional sample of 1, 200 adult inpatients, hospitalized (>24 hrs) in 6 hospitals, and receiving at least 1 antibiotic dose on 4 index dates chosen at equal intervals through a 1-year study period (October 1, 2009–September 30, 2010). METHODS: Infectious disease specialists recorded patient demographic characteristics, comorbidities, microbiological and radiological testing, and agents used, dose, duration, and indication for antibiotic prescriptions. RESULTS: On the index dates 4, 119 (60.5%) of 6, 812 inpatients were receiving antibiotics. The random sample of 1, 200 case patients was receiving 2, 527 antibiotics (average: 2.1 per patient); 540 (21.4%) were prophylactic and 1, 987 (78.6%) were therapeutic, of which 372 (18.7%) were pathogen-directed at start. Of the 1, 615 empirical starts, 382 (23.7%) were subsequently pathogen-directed and 1, 231 (76.2%) remained empirical. Use was primarily for respiratory (27.6% of prescriptions) followed by gastrointestinal (13.1%) infections. Fluoroquinolones, vancomycin, and antipseudomonal penicillins together accounted for 47.1% of therapy-days. CONCLUSIONS: Use of broad-spectrum empirical therapy was prevalent in 6 US acute care facilities and in most instances was not subsequently pathogen directed. Fluoroquinolones, vancomycin, and antipseudomonal penicillins were the most frequently used antibiotics, particularly for respiratory indications. Infect. Control Hosp. Epidemiol. 2015;37(1):70–79